2019
DOI: 10.2196/10855
|View full text |Cite
|
Sign up to set email alerts
|

Training Cognitive Functions Using Mobile Apps in Breast Cancer Patients: Systematic Review

Abstract: BackgroundBreast cancer is an invalidating disease and, in particular, its treatment can bring serious side effects that have a physical and psychological impact as well. Specifically, cancer's treatment generally has a strong impact on cognitive function. In the last years, new technologies and eHealth had proved to have a growing influence on health care and innovative mobile applications can be a useful tool to deliver cognitive exercise in the patient's home.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 70 publications
0
17
0
Order By: Relevance
“…Second, if ET leads to significant cognitive impairment, adherence to medication may be easily compromised. Third, specific supportive treatments (training strategies) should be used if such effects of therapy are identified (25,26).…”
mentioning
confidence: 99%
“…Second, if ET leads to significant cognitive impairment, adherence to medication may be easily compromised. Third, specific supportive treatments (training strategies) should be used if such effects of therapy are identified (25,26).…”
mentioning
confidence: 99%
“…The development and delivery of home-based or web-based interventions may have advantages over traditional clinic–based interventions. However, there is a scarcity of innovative interventions for cognitive training [ 41 •]. A recent review showed that, to date, none of these were specifically developed for BC patients [ 41 •].…”
Section: Cognitive Impairmentmentioning
confidence: 99%
“…In recent years, the shift toward a “patient-centered care approach” already led to a greater importance of patients’ contribution in the medical decision-making process. The increase of patient agency within their own care process originates from elements that can be considered as enablers of patient empowerment15,16 toward a shared decision-making approach that may be considered the best expression of the patient-centered approach in the clinical context 17. In the shared decision-making process, patient and physician, as well as health care providers, develop a partnership 18,19…”
Section: The Patient Rolementioning
confidence: 99%